Interest of longitudinal patellar tunnels in reconstructing chronic patellar tendon rupture with semitendinosus autograft: A case report - Aymen Ben Fredj; Hedi Rbai; Farouk Chatbouri; Marouene Berriri; Abderrahmen Daadoucha; Anouar Boughattas (Trauma Case Reports, 2024)
Treatment of chronic patellar tendon ruptures represents a real challenge for orthopaedic surgeons. The superior patellar migration and the pathological aspect of the tendon are the two conditions that aggravate the situation. Several reconstruction methods have been described in the literature. Hamstring tendon augmentation using horizontal patellar tunnel is widely used in such cases. However, underuse of longitudinal patellar tunnels, although they reproduce the native footprint of the patellar tendon insertion, highlights a missed opportunity in chronic patellar tendon rupture reconstruction. In the current article, we describe a semitendinosus tendon autograft reconstruction technique where the patellar tunnels are drilled longitudinally instead of being drilled transversely from medial to lateral. At 34 months follow-up, our patient claimed full active knee mobility with good quadriceps strength. Reproducing the native footprint of the patellar tendon insertion, through longitudinal patellar tunnels, leads to optimal outcomes after chronic patellar tendon rupture reconstruction with Semitendinosus Autograft.